APPLICATION OF DIGITAL TECHNOLOGIES IN TRANSLATION EDUCATION PROGRAMS (Journal of Contemporary Philology, 2018)
As a result of digital innovations, apart from professional competences acquired bythe students with the completion of their studies, it is also necessary for them todevelop a range of other skills, in particular technical skills in order to become morecompetitive on the labour market. Specifically, it is important for translators to acquireso-called digital competences or an ability to use digital technologies in the translationprocess. The translation industry is undergoing tremendous transformation due to thegrowing use of digital technologies and as a result changes are subsequently neededin translation studies offered at university level with a shift from conventional teaching methods and passive learning to contemporary teaching methods and interactivelearning.The subject of research in this paperinvolvesdigital competences ofstudents; namely,the paper analyses whetherstudents use digitaltechnologies in thetranslation process and the level of their awareness on the importance of digital skillsfor translators. For the purpose of this paper a survey is conducted among 26 studentsattending translation studies at Department of Translation and Interpreting within theFaculty of Philology in Skopje. The conclusions based on the results of this researchindicate possibilities and methods for improvement of translator education by use ofdigital technologiesand digital communication, whereas special emphasis is put onthe need for digitalisation of the practical classes and of the learning resources.
Keywords: translation teaching; digital technology; translator transversal competences